A checklist of Norwegian Tardigrada - Terje Meier (Fauna Norvegica, 2017)
Animals of the phylum Tardigrada are microscopical metazoans that seldom exceed 1 mm in length. They are recorded from terrestrial, limnic and marine habitats and they have a distribution from Arctic to Antarctica. Tardigrades are also named ‘water bears’ referring to their ‘walk’ that resembles a bear’s gait. Knowledge of Norwegian tardigrades is fragmented and distributed across numerous sources. Here this information is gathered and validity of some records is discussed. In total 146 different species are recorded from the Norwegian mainland and Svalbard. Among these, 121 species and subspecies are recorded in previous publications and another 25 species are recorded from Norway for the first time.